Health equity profile of knee replacement patients in the South African public sector: A descriptive study - Marisa Coetzee; Amanda M. Clifford; Jacobus D. Jordaan; Quinette A. Louw (AOSIS, 2024)
Background: Knee replacement surgery can significantly improve the quality of life of patients with severe knee osteoarthritis. Equitable access to knee replacement surgery is important to ensure that everyone, regardless of their socioeconomic status or geographical location, have fair and timely access. Objectives: The aim of our study was to (1) describe the health equity profile and quality of life of patients awaiting knee replacement at a single academic hospital in South Africa and to (2) describe the association between these health equity factors and the waiting time. Method: A cross-sectional survey and retrospective record review of patients awaiting knee replacement was conducted using the PROGRESS-Plus health equity framework. Chi-square statistics were used to calculate association between health equity factors and the waiting time. Results: Three-hundred and two (N = 302) patients (77% female; mean age 67 years) participated, of whom one in three patients waited 5 years or longer for surgery. Elderly patients ( 70 years) and patients from lower socio-economic background were less likely to have equitable access to surgery. Conclusion: The current screening protocol for knee replacement surgery in the public health care sector does not provide equitable access to surgery. A more holistic screening approach alongside selective surgical prioritisation and rehabilitation could reduce the waiting list and facilitate equitable access to care. Clinical implications: Health equity factors such as socioeconomic status, age, and other patient characteristics such as life roles and employability should be taken into consideration when screening patients for elective knee replacement waiting lists.